WAYS TO INCREASE THE ECONOMIC POTENTIAL OF ENTERPRISES OF THE TEXTILE INDUSTRY OF THE REPUBLIC OF UZBEKISTAN ON THE BASIS OF INTEGRAL EVALUATION (CAHIERS MAGELLANES-NS, 2024)
The article considers the potential of textile enterprises in terms of assessing its elements and their impact on the economic activity of the organization, and based on the results developed recommendations for increasing the economic potential of the textile enterprise. An integral indicator was used in assessing the economic potential of textile enterprises, and based on the results of the assessment, recommendations were made to increase the economic potential of the enterprise. The use of the valuation method helps to closely look for opportunities to increase economic potential.